Revealing Women’s Suffering through Displacing Meaning in William Blake’s Poems - Andi Ramadhan; Wahyuni Wahyuni; Jepri Jepri (Prologue: Journal on Language and Literature, 2021)
This thesis explores the displacing meaning to reveal women’s suffering in William Blake’s poems such as: “The Sick Rose”, “Earth’s Answer”, “My Pretty Rose Tree”, “London” and “Ah Sunflower”. There are two objectives of this research, they are to find the types of displacing and to find the displacing meaning to reveal women’s suffering. The theory used in this research is the semiotic analysis using Riffaterre’s theory of displacing meaning caused by metaphor and metonymy in the form of personification, simile, and synecdoche in his book Semiotics of Poetry. The methodology employed is qualitative research in which the researcher tried to present the issues descriptively. As for the data, they were collected from the displacing meaning. The poems were taken out as the primary data. The results of the research, the researcher found that the types of displacing meaning in thematic William Blake’s poem caused by metaphor, metonymy, personification, synecdoche, and the displacing meaning reveal women’s suffering in the form of mental and physical suffering which includes sadness, disgust, selfishness, restraints, jealousy, fear, abuse, violence, unsound, evil, death, poverty, and disease.